Modelagem da dispersão de odor no ar proveniente de efluente têxtil utilizando o software AERMOD - SANTOS, Patrícia Nazaré Ferreira dos (2022)
Pollution generated by gaseous emissions and industrial effluents is a problem for the balance of the environment and for public health. The textile industries are considered one of the major responsible for the pollution of rivers and air, in addition to the consumption of high volumes of water. This problem is aggravated in the semi-arid region of the state of PE, which has a great scarcity of water resources. In the Local Productive Arrangement (APL) effluents with high rates of organic matter are generated, responsible for the high odor content in the atmospheric air, mainly due to anaerobic decomposition generating nitrogen and sulfur compounds. These odorant gases are composed of a mixture, with hydrogen sulfide (H2S) being the gas represented in the odor dispersion simulation. This work estimated the dispersion of odors in the air using the AERMOD Software by applying data from a water treatment plant of textile origin located in the rural region of Pernambuco. The techniques used to evaluate the intensity of the odor and its atmospheric dispersion were the sensory method of olfactometry, combined with the method of modeling atmospheric dispersion AERMOD. The averages found for annual concentrations in 2019 and 2020 were 10 OU/m3. In Brazil, there is no applicable legislation for odorous substances, so the study results are only indicative and have no legal effect. Monitoring studies on the dispersion of odorous gases by AERMOD simulation are important because they can prevent risks of inhalation of chemicals, protect the environment and reduce future costs to public health.